Role of BMP-4 and Its Signaling Pathways in Cultured Human Melanocytes - Hee-Young Park; Christina Wu; Mina Yaar; Christina M. Stachur; Marita Kosmadaki; Barbara A. Gilchrest (International Journal of Cell Biology)
Bone Morphogenetic Protein (BMP-4) was shown to down-regulate melanogenesis, in part, by decreasing the level of tyrosinase [Yaar et al. (2006) JBC:281]. Results presented here show that BMP-4 down-regulated the protein levels of TRP-1, PKC-β, and MCI-R. When paired cultures of human melanocytes were treated with vehicle or BMP-4 (25 ng/ml), MAPK/ERK were phosphorylated within one hour of BMP-4 treatment. Then the activated MAPK/ERK caused an acute phosphorylation of MITF, followed by proteosome-mediated degradation of MITF, the key transcription factor for melanogenic proteins [Wu et al. (2000) Gene & Development:14]. However, prolonged exposure of melanocytes to BMP-4 (up to 48 hours) caused a decrease in the level of MITF-M transcript. In addition, BMP-4 decreased the intracellular level of cAMP, the key regulator of MITF expression. These results demonstrate that BMP-4 activates MAPK/ERK signaling pathway to transiently activate MITF; however, chronic treatment of BMP-4 to melanocytes causes a down-regulation of the expression of MITF, possibly in a cAMP-dependent pathway.